Evaluating Thermal Regime of Cold Region Roads for Climate Change Adaptation - Liu, Michelle (University of Waterloo, 2020)
Nearly a quarter of the Northern Hemisphere is underlain with permafrost, of which discontinuous permafrost is most sensitive to the temperature of its surrounding. Climate change and the implementation of infrastructure have combined effects on the thermal regime of permafrost, leading to thaw settlement that can be detrimental to structures. In Northern Canada and Alaska, permafrost degradation is leading to unprecedented spending on maintenance and rehabilitation of linear infrastructure. Although a number of permafrost protection techniques for road structures have emerged in recent decades, their costs remain high and rate of implementation remains low. This predicament can be attributed to the lack of studies that compare the feasibility and performance of these techniques. There is also only a low number of field studies that examine the in situ thermal regime of permafrost influenced by both climate change and infrastructure, which further contributes to the uncertainty surrounding many of the permafrost protection techniques. In light of these gaps, this study conducted a literature scan for qualitative feasibility comparison of existing permafrost protection techniques, simulated the performance of select techniques in TEMPS for comparison, and examined the in situ thermal regime through a field study along the Ingraham Trail (NWT Highway 4) in Yellowknife, Northwest Territories. Based on existing literature, reflective surfaces, shading, ventilation pipes, thermosyphons, air convection, geosynthetics, pre-thawing, and heat-dissipating structures and materials are deemed suitable for high-temperature (discontinuous) permafrost, while embankment insulation was deemed suitable for low-temperature (continuous) permafrost. Most heat-dissipating pavement structures, like unilateral heat transfer pavement, may be suitable for both high- and low-temperature permafrost, though further studies are required. It was concluded from this review that most permafrost protection techniques available at the moment are ...